THE FORMATION OF A PROJECT RISK MANAGEMENT SYSTEM OF INDUSTRIAL ENTERPRISES - David M. Mashkov (Статистика и экономика, 2016)
In the article the author systematizes thestages of evolutionary development of thescience of risk management, problems ofdevelopment of domestic machine building and proposed activities improve riskmanagement of industrial enterprises.In the work developed adequate to themodern state of the industrial productiontools in the risk management system ofthe enterprise.